Evaluación de las normas de bioseguridad del departamento de vacunación de la Dirección Distrital de Salud N-09D13 cantón Balzar, año 2013 - Alcívar Barreto, Edita Elaine (2014)
His research was conducted at the Balzar Canton is located in the northeastern part of the province of Guayas. To the north the canton El Empalme the south by the canton Colimes the east by the province of Los Rios , and on the west by the province of Manabí in the health district N- 09D13 at the vaccination site that is located in Avenue student and Vince, in ancient times was a thriving village that was planned ahead, a few seat ancestry families who had come to seek his fortune , for it was presented as objective evaluation of biosafety regulations of the Department Vaccination of the District Health Directorate N- 09D13 Balzar Canton in 2013. The methods applied were descriptive, analytic and synthetic (deductive and inductive) for the problem. The universe of study make up the 2 public officials working in District Health Directorate N- 09D13 canton Balzar and citizenship, it was necessary to apply the formula of probability 5 % error and 95 % chance to give shown as 383 users, which were applied surveys as tools for collecting the information needed in the development of this research to staff a survey to know the criteria on the subject under study was also applied. The implementation of the research was based on non-parametric statistical non-experimental same which allowed to obtain the results, conclusions and recommendations. In question 4 it has been possible to establish that a 86% requests the vaccination service between 5-6 times per year, in the question the 86% said they did not know whether or not to apply the vaccines of agreements to the regulations and in the question 9 the 100% agree that develop a biosafety manual The proposal includes the development of a Biosafety Manual for the department immunization of the District Health Directorate N- 09D13 Canton Balzar, it is structured according to the specifications suggested by the supervisory bodies of such entities public and complies with the methodology of writing . The implementation of the Biosafety Manual department immunization of the District Health Directorate N- 09D13 Canton Balzar , material, financial, administrative and eminently human resources required; being necessary investment in technology resources , stationery and staff training section in question.